2019
DOI: 10.1002/ldr.3334
|View full text |Cite
|
Sign up to set email alerts
|

Perianth and abiotic factors regulate seed germination of Haloxylon stocksii—A cash crop candidate for degraded saline lands

Abstract: Haloxylon stocksii, a common succulent halophyte of saline flats in Pakistan and adjacent countries, is utilized as forage, washing soda, and medicines by the local people. In addition, its cultivation can also prevent land degradation by erosion and salinity. Given that information about its seed ecology is limited, this study aimed to unveil the germination requirements of H. stocksii seeds. Seed morpho‐physical features and effects of perianth persistence, salinity (0–500‐mM NaCl), photoperiod (12 hr light/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 56 publications
1
15
0
Order By: Relevance
“…High soil salinity can inhibit seed germination via osmotic effect and toxic effect ( Gul et al, 2013 ; Song et al, 2017 ). Although the toxic effects on the hydrated seeds of halophytes have been reported, the decline in germination caused by salinity is primarily osmotic effect ( Rasheed et al, 2019 ). For example, the brown seeds of S. aralocaspica can germinate to 10% at 1400 mM NaCl.…”
Section: Introductionmentioning
confidence: 99%
“…High soil salinity can inhibit seed germination via osmotic effect and toxic effect ( Gul et al, 2013 ; Song et al, 2017 ). Although the toxic effects on the hydrated seeds of halophytes have been reported, the decline in germination caused by salinity is primarily osmotic effect ( Rasheed et al, 2019 ). For example, the brown seeds of S. aralocaspica can germinate to 10% at 1400 mM NaCl.…”
Section: Introductionmentioning
confidence: 99%
“…Plants living in arid regions are expected to experience high levels of drought stress (Cui et al, 2019;Rasheed et al, 2019). Our results indicate that seeds of A. venetum and A. pictum have high drought tolerance and show differential characteristics.…”
Section: Discussionmentioning
confidence: 78%
“…Seed germination is the most critical transition period for crop establishment, especially under adverse abiotic conditions (Campobenedetto et al, 2020). Successful establishment of seedlings largely depends on timely germination and uniform emergence under different abiotic stresses such as drought and salinity (Rasheed et al, 2019). Although studies focusing on germination have been undertaken for A. venetum and A. pictum seeds, the majority of investigations have used freshly matured seeds and under a single environmental factor (Shi et al, 2014;Liu et al, 2015;Xu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sosa et al (2005) suggested that salt ion effects would have less influence on seed germination in Prosopis strombulifera than the soil water content. Comparable constatations were also drawn on the seed germination of Chenopodium glaucum (Duan et al, 2004), Suaeda vermiculata (El-Keblawy et al, 2018), Haloxylon stocksii (Rasheed et al, 2019) and Prosopis pallida (Aljasm et al, 2021). Zehra et al (2013) reported the germination inhibition in Phragmites karka by using different salts of sodium, magnesium and potassium.…”
Section: Salt and Drought Effect On Germination And Initial Growth Of...mentioning
confidence: 97%